Finding the bad actor: Challenges in identifying toxic constituents in botanical dietary supplements. (February 2019) - Roberts, Georgia K.; Gardner, Dale; Foster, Paul M.; Howard, Paul C.; Lui, Edmund; Walker, Larry; van Breemen, Richard B.; Auerbach, Scott S.; Rider, Cynthia
Abstract: Botanical-derived dietary supplements have widespread use in the general population. The complex and variable nature of botanical ingredients and reports of adverse responses have led to concern for negative human health impacts following consumption of these products. Toxicity testing of the vast number of available products, formulations, and combinations is not feasible due to the time and resource intensive nature of comprehensive testing. Methods are needed to assess the safety of a large number of products via more efficient frameworks. Identification of toxicologically-active constituents is one approach being used, with many advantages toward product regulation. Bioassay-guided fractionation (BGF) is the leading approach used to identify biologically-active constituents. Most BGF studies with botanicals focus on identifying pharmacologically-active constituents for drug discovery or botanical efficacy research. Here, we explore BGF in a toxicological context, drawing from both efficacy and poisonous plant research. Limitations of BGF, including loss of mixture activity and bias toward abundant constituents, and recent advancements in the field (e.g., biochemometrics) are discussed from a toxicological perspective. Identification of active constituents will allow better monitoring of market products for known toxicologically-active constituents, as well as surveying human exposure, two important steps to ensuring the safety of botanical dietary supplements. Highlights: Safety of botanical products would be improved by identification and monitoring of potentially toxic constituents. Adulteration and natural variation contribute to the complexity of botanicals and potential toxic constituents. Identification of toxic constituents uses bioassay guided fractionation and complementary approaches. Known mechanism of toxicity improves efficiency in identification of actives. Suspected toxic constituents can be screened using targeted approaches.